2018
DOI: 10.1088/1361-6560/aae1bb
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam CT reconstruction with gravity-induced motion

Abstract: Fixed-gantry cone-beam computed tomography (CBCT), where the imaging hardware is fixed while the subject is continuously rotated 360° in the horizontal position, has implications for building compact and affordable fixed-gantry linear accelerators (linacs). Fixed-gantry imaging with a rotating subject presents a challenging image reconstruction problem where the gravity-induced motion is coupled to the subject's rotation angle. This study is the first to investigate the feasibility of fixed-gantry CBCT using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…One technique to achieve this is to sort image projections into bins based on their angle and reconstruct each bin independently. Similar techniques are used to reconstruct respiratory‐correlated CBCT images with each projection sorted into respiratory phase bins . We have previously shown using anesthetized and immobilized rabbits rotated horizontally that this reconstruction technique can account for gravity‐induced motion, resulting in images with less than 1 mm of motion blur …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One technique to achieve this is to sort image projections into bins based on their angle and reconstruct each bin independently. Similar techniques are used to reconstruct respiratory‐correlated CBCT images with each projection sorted into respiratory phase bins . We have previously shown using anesthetized and immobilized rabbits rotated horizontally that this reconstruction technique can account for gravity‐induced motion, resulting in images with less than 1 mm of motion blur …”
Section: Discussionmentioning
confidence: 99%
“…Similar techniques are used to reconstruct respiratory‐correlated CBCT images with each projection sorted into respiratory phase bins . We have previously shown using anesthetized and immobilized rabbits rotated horizontally that this reconstruction technique can account for gravity‐induced motion, resulting in images with less than 1 mm of motion blur During treatment delivery, a static shift of the radiation beam (or a patient shift) could be used to compensate for motion of the target volume resulting from patient rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar anatomic deformation has also been shown in single organ and animal studies, where the anatomical deformation caused by horizontal rotation led to artefacts in the fixed-gantry CBCT reconstruction (Feain et al, 2016;Barber et al, 2018). Shieh et al developed an algorithm for compensating for gravity induced motion for fixed-beam CBCT scans which was tested on anaesthetised rabbits (Shieh et al, 2018). However, this algorithm A c c e p t e d M a n u s c r i p t compensated for only the rigid motion, and not for any complex deformable motion.…”
Section: Introductionmentioning
confidence: 65%
“…However, this algorithm A c c e p t e d M a n u s c r i p t compensated for only the rigid motion, and not for any complex deformable motion. It has been shown previously that for both humans (Whelan et al, 2017) and rabbits (Barber et al, 2018;Shieh et al, 2018), the non-rigid deformation makes up a significant component of the gravity-induced motion caused by horizontal rotation. Additionally, the authors reported that for one of the rabbits, the reconstruction of the volume using their motion compensation algorithm had significant motion blur, caused by the large motion that occurred during rotation.…”
Section: Introductionmentioning
confidence: 99%
“…We have integrated two image guidance algorithms that allows the magnitude of target motion due to gravitational deformation to be measured during rotation. These algorithms are motion compensated cone-beam CT (CBCT) reconstruction 12 (labelled 1 in Figure 1) and real-time Kilovoltage Intrafraction Monitoring (KIM) 13 (labelled 2 in Figure 1). Analogous to conventional radiotherapy, the motion compensated cone-beam CT algorithm was used to verify patient position prior to treatment delivery, while KIM measured the target position in real-time as the patient is rotated to each beam angle.…”
Section: Introductionmentioning
confidence: 99%